Control of immune cell entry through the tumour vasculature: a missing link in optimising melanoma immunotherapy?. Issue 3 (17th March 2017) - Tan, Lih Yin; Martini, Carmela; Fridlender, Zvi G; Bonder, Claudine S; Brown, Michael P; Ebert, Lisa M
Abstract : Metastatic melanoma remains a fatal disease to many worldwide, even after the breakthrough introduction of targeted therapies such as BRAF inhibitors and immune checkpoint blockade therapies such as CTLA‐4 and PD‐1 inhibitors. With advances in our understanding of this disease, as well as the increasing data gathered from patient studies, the significance of the host immune response to cancer progression and response to treatment is becoming clear. More specifically, the presence of intratumoral CD8 + cytotoxic T‐cells correlates with better prognosis whereas the accumulation of monocytes/macrophages and neutrophils in the tumour is often associated with worse prognosis. Access and infiltration of circulating leukocytes into the tumour is governed by adhesion molecules and chemokines expressed by the endothelial cells of the vasculature. This review focuses on the adhesion molecules and chemokines which control the homing of CD8 + cytotoxic T‐cells, monocytes and neutrophils to peripheral tissues, including tumours. We discuss the role of these leukocyte subsets in regulating melanoma growth, and detail the mechanisms used by tumours to selectively recruit or exclude these leukocytes for their own advantage. In doing so, we bring to light an underappreciated component of tumour biology which should be considered in combination with current treatments to selectively alter the leukocyte composition of tumours and ultimately enhance treatment outcome.